Sustainable community development in Northern Communities : applications for affordable housing in the Yukon - Huffman, Clarissa (2021)
By exploring the perceptions and experiences of Yukoners living in Dawson City and Whitehorse, YT, this research discusses planning challenges in the Yukon and their influence on community sustainability. Analysis of planning policy revealed aspirational rather than action-oriented language, and interviews with residents identified three barriers to change: the role of culture, insufficient environmental education, and lack of personal responsibility. The culmination of this project is seven practical recommendations designed to improve community sustainability outcomes. The recommendations include thoughtfully incorporating local context through program design, demonstrating commitment to sustainability, balancing local knowledge and innovation, effectively developing public land, prioritizing economic diversification, ensuring the relevance of zoning bylaws, and promoting non-vehicular travel appropriate for cold-weather climates. By implementing these recommendations, Yukon communities may find they are more capable of responding to exogenous shocks, and also that this can come with the co-benefit of increased housing affordability.